Real-time tracking reveals catalytic roles for the two DNA binding sites of Rad51 - Kentaro Ito (Nature Portfolio, 2020)
Rad51 drives DNA strand exchange, the central reaction in recombinational DNA repair. Two sites of Rad51 are responsible for DNA binding, but the function of these sites has proven elusive. Here, the authors employ real-time assays to reveal catalytic roles for the two DNA binding sites of Rad51.